Penyuluhan Budidaya Jamur dalam Pemanfaatan Tongkol Jagung di Desa Simpang Agung Kabupaten OKU Selatan - Siti Anisatur Rofiqah; Dwi Andriani; Effendi Effendi (Jurnal Indonesia Mengabdi, 2020)
This devotion is conducted because haven’t been there utilization of corncops waste to be mushroom cultivation at Simpang Agung Village in South OKU districts, even though 90% of society plant the corns. Lignin and selulose in the corns can be useful to cultivate mushroom. All this time corn cops in Simpang Agung is only burned and discarded, never processed to be high value food sources. Some procedures solutions conducted to the society about corncops waste treatment to be mushroom is giving knowledge by socialization, training, and monitoring. The result of this training is corn cops waste processed by special simple technology to be mushroom that can be consumed by society. Accurate management can give economic benefits to the society so that can increase standard of living.